Hysteroscopic myomectomy outcomes after 3-month treatment with either Ulipristal Acetate or GnRH analogues: a retrospective comparative study. (March 2016) - Sancho, Javier Monleón; Delgado, Verónica Serrano de la Cruz; Valero, Maria José Nuñez; Soteras, Marta Gurrea; Amate, Vicente Payá; Carrascosa, Antonio Abad
Abstract: Ulipristal Acetate (UPA) modifies the endometrium, as well as fibroids, and therefore it might make hysteroscopic surgery more difficult. To confirm that pre-treatment with UPA is as safe and effective an option as pre-treatment with GnRH analogues, considered the gold standard. We present the first series of 26 hysteroscopic myomectomies after 3 months treatment with UPA and we compare the results with a series of 24 cases pretreated with GnRH analogues. This was a retrospective cohort study between July 2013 and May 2015. We analyszed patients with submucous myomas >2.5 in diameter. Hysteroscopic myomectomy was performed after 3 months of treatment with either UPA (5 mg daily) or the GnRH agonist (3.75 mg/month). Both groups were similar in age, myoma initial size and classification. There were no significant differences between UPA and GnRHa treated groups in terms of percentage of myomas resected (93% vs 98%), duration of surgery (38 vs 37 min), fluid deficit (200 vs 350 ml) and complications. In the surgeon's subjective opinion, UPA treatment was associated with an easier resection. Based on our experience, previous treatment with UPA does not difficult Hhysteroscopic myomectomy. Endometrial changes have no impact on surgery. Safety and feasibility are comparable to hysteroscopic myomectomies with previous treatment with GnRH analogues. This allows us to take advantage of the reduction in size of fibroids before surgery with less side effects.